Lactate Dehydrogenase activity and Isoenzyme Patterns in the Developing Skeletal Muscles of Sialoadenectomised Female Mice - Walvekar, Madhuri. V.; Bhopale, Lata. P.; Pol, Suvarna. B. (Asian Journal of Biological and Life Sciences, 2013)
Lactate dehydrogenase (LDH) is essential for anaerobic glycolysis, catalyses the interconversion of lactate and pyruvate, critical for meeting rapid high energy demands and hence is necessary for muscular contraction in absence of oxygen. Objective of present study was to assess whether the polypeptides secreted by submandibular gland affect the physiology of developing skeletal muscles or not. For this study female mice at the age of twenty days were sialoadenectomised (removal of submandibular glands), when the submandibular gland starts the secretion of growth factors. The operated female mice were maintained under normal condition in the departmental animal house upto the age of 40 days, 60 days, 80 days and 100 days. Lactate dehydrogenase activity and electrophoretic separation of LDH from gastrocnemius, soleus and rectus abdominus muscles were determined in sialoadenectomised and control female mice in all four groups. Lactate dehydrogenase activity from all the three muscles was increased in sialoadenectomised mice as compared to control mice in all four groups. The electrophoretic separation of LDH also demonstrated the increase in intensity of LDH bands especially LDH-V in all the three muscles of sialoadenectomised mice. Thus, increase in LDH activity, especially LDH-V indicates anaerobic condition in muscle and also pathological conditions in the muscle due to sialoadenectomy.